Revised Description of the Early Permian Recumbirostran “Microsaur” Nannaroter mckinziei Based on New Fossil Material and Computed Tomographic Data - MacDougall, Mark J.; Seeger, Robert; Gee, Bryan; Ponstein, Jasper; Jansen, Maren; Scott, Diane; Bevitt, Joseph J.; Reisz, Robert R.; Fröbisch, Jörg (Frontiers in Ecology and Evolution, 2021)
The early Permian Richards Spur locality of Oklahoma has produced abundant material of numerous terrestrial fossil tetrapods, including various “microsaurs,” several of which are considered to belong to the clade Recumbirostra. We present a new partial skull of the recumbirostran “microsaur” Nannaroter mckinziei; through computed tomography (CT) analysis of both this new specimen and the holotype, we provide an updated description of the taxon. This new description provides novel information regarding several regions that could not be examined previously due to either being absent in the holotype or difficult to access. This includes missing and obscured aspects of the skull roof, braincase, lower jaw, and the palatal region. Furthermore, the new information obtained from this description was used to update phylogenetic character codings of Nannaroter, and a revised phylogenetic analysis was conducted. The results of this updated analysis are congruent with those of other recent phylogenetic analyses of recumbirostran “microsaurs.” This new information adds to the ever-growing body of early tetrapod CT data, which has been, and will continue to be, important in revealing details regarding early tetrapod anatomy, interrelationships, paleoecology, and evolution.